2009
DOI: 10.3748/wjg.15.1650
|View full text |Cite
|
Sign up to set email alerts
|

A combination treatment of entecavir and early-phase corticosteroid in severe exacerbation of chronic hepatitis B

Abstract: Of patients with severe exacerbation of chronic hepatitis B accompanied by jaundice and coagulopathy, 20%-30% have a fatal outcome. In this report, we describe 2 cases of severe exacerbation of chronic hepatitis B with jaundice and coagulopathy who were successfully treated with a combination of entecavir and corticosteroid. In both cases, rapid reductions in serum hepatitis B virus (HBV)-DNA levels were observed, and corticosteroid was stopped after serum HBV-DNA levels became undetectable. Entecavir treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…This case report supports our previous studies [14,15]. Matsumoto et al [25] stopped CS after HBV DNA became undetectable, and as a result, the periods of immunosuppression were sufficient, at 10 and 12 weeks, respectively. We suppose that the periods could be shortened as described above in order to avoid infectious complications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This case report supports our previous studies [14,15]. Matsumoto et al [25] stopped CS after HBV DNA became undetectable, and as a result, the periods of immunosuppression were sufficient, at 10 and 12 weeks, respectively. We suppose that the periods could be shortened as described above in order to avoid infectious complications.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Matsumoto et al [25] reported 2 patients with severe exacerbation of chronic hepatitis B with coagulopathy who were treated with a combination of ETV and early-phase CS, based on our previous report. Although one patient met our criteria and the other did not, without jaundice, and the durations from clinical onset to the administration of the combination therapy were not described, both patients recovered successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is conceivable that NAs used on its own has limits to resolution of the serious conditions. And early combined intervention with corticosteroid, which can modulate the activity of chronic hepatitis B by suppressing the host-immune response to HBV antigens, might be rational [5], [27], [28]. However, this data was restricted to short term (less than 1 year) observation, and was likely related to presumed duration of AE.…”
Section: Discussionmentioning
confidence: 97%
“…Severe acute exacerbation (SAE) presented with high ALT levels accompanied by jaundice can also be seen in approximately 15%–37% of CHB patients in 4 years [4]. These exacerbations may progress to acute on chronic liver failure with high potential mortality [5]. To date, no specific therapy is established for this critical scenario from chronic hepatitis to fulminate hepatic failure owing to AE.…”
Section: Introductionmentioning
confidence: 99%
“…Matsumoto et al described two cases of severe exacerbations of chronic hepatitis B with jaundice and coagulopathy, which were successfully treated with a combination of entecavir (0.5 mg/day) and prednisolone (30 or 50 mg/day) 25. In both cases, the patients reported a rapid reduction in serum HBV DNA levels and a clearance of viral load was reached after 12–15 weeks of treatment.…”
Section: Entecavir In Patients With Severe Forms Of Hepatitis Bmentioning
confidence: 99%